Benthic aerobic respiration and nutrient fluxes in Cananéia-Iguape Estuarine-Lagoon complex along a salinity gradient - Paula C. Moraes; Bruno O. Sutti; Vitor G. Chiozzini (Ocean and Coastal Research)
Estuaries are important features for global biogeochemical understanding, due to their highly coupled interaction between sediment and water. In those places, the land-sea transect sometimes has a gradient of physical and chemical characteristics, influencing the availability of nutrients and consequently primary production. This study aimed to observe the benthic aerobic respiration and sediment-water nutrient fluxes in a freshwater to marine transect in the Cananéia-Iguape Estuarine-Lagoon Complex (CIELC) on the southeastern Brazilian Coast. This area contains the most pristine mangrove at the limit between tropical and subtropical zones, providing an ideal observatory for ecological research programs. Intact sediment cores were incubated in laboratory to determine fluxes of O2 , TCO2 , and dissolved nutrients. Three different sites with different salinities were sampled during the four seasons of the year. Sediment characteristics of the sites were compared, showing higher organic matter in the lowest saline (LS) site and higher phytopigments in the highest saline (HS) site, as expected. Benthic aerobic respiration, O2 and CO2 fluxes, ranged from −0.4 to −3.2 mmol m−2 h−1 and 0.1 to 1.5 mmol m−2 h−1, respectively, and exhibited statistically significant variations between seasons and in a salinity gradient. Dissolved inorganic nitrogen and silicate, ranging from −228.7 to 544.8 μmol m−2 h−1 and −205.8 to 4,173.5 μmol m−2 h−1, respectively, were generally released from the sediment, whereas phosphate ranged from −25.2 to 29.6 μmol m−2 h−1 with more variation in time and space. The LS site was characterized as a nitrogen sink and a silicate and phosphate releaser, and the HS site was characterized as a nitrogen producer and a phosphorus consumer. However, seasonal and spatial variations were observed, and the interaction between space and time factors was always highly significant, indicating that the metabolic behavior of the benthic compartment depends on both trophic and physicochemical conditions.